2021
DOI: 10.1186/s40168-021-01098-7
|View full text |Cite
|
Sign up to set email alerts
|

Breed differences in the expression levels of gga-miR-222a in laying hens influenced H2S production by regulating methionine synthase genes in gut bacteria

Abstract: Background The microbiota in the cecum of laying hens is crucial for host digestion, metabolism, and odor gas production. The results of recent studies have suggested that host microRNAs (miRNAs) can regulate gene expression of the gut microbiota. In the present study, the expression profiles of host-derived miRNAs in the cecal content of two laying hen breeds; Hy-line Gray and Lohmann Pink, which have dissimilar H2S production, were characterized; and their effects on H2S production by regulat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…Low H 2 S content protects the body and helps in the self-regulation of intestinal cells, including inflammation and intestinal epithelial tissue regeneration. 41 In contrast, high H 2 S content is carcinogenic to intestinal epithelial cells and can cause a series of negative effects, such as colon cell apoptosis, villus contraction, mucosal depletion, and reactive cryptcell proliferation, further causing colitis. Excessive H 2 S can also inhibit the oxidation of butyrate in colon cells, which is particularly significant in ulcerative colitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low H 2 S content protects the body and helps in the self-regulation of intestinal cells, including inflammation and intestinal epithelial tissue regeneration. 41 In contrast, high H 2 S content is carcinogenic to intestinal epithelial cells and can cause a series of negative effects, such as colon cell apoptosis, villus contraction, mucosal depletion, and reactive cryptcell proliferation, further causing colitis. Excessive H 2 S can also inhibit the oxidation of butyrate in colon cells, which is particularly significant in ulcerative colitis.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrogen sulfide is mainly produced by sulfate‐reducing bacteria, such as Firmicutes and Proteus , by metabolizing mucin, amino acids, and other sulfur compounds. Low H 2 S content protects the body and helps in the self‐regulation of intestinal cells, including inflammation and intestinal epithelial tissue regeneration 41 . In contrast, high H 2 S content is carcinogenic to intestinal epithelial cells and can cause a series of negative effects, such as colon cell apoptosis, villus contraction, mucosal depletion, and reactive cryptcell proliferation, further causing colitis.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, previous studies have indicated that miRNAs can promote the growth of certain microbes and improve the production of their metabolites. 12–15 , 38 Here, we enriched the regulatory mechanisms and mode of action of miRNAs on microbes, as we found that miRNAs could also exert suppressive effects on microbial growth and metabolism. However, the detailed mechanisms by which miRNAs exert a suppressive or promoting effect on microbes require further studies.…”
Section: Discussionmentioning
confidence: 99%
“…As transcriptional regulators, microRNAs (miRNAs) play a significant role in various physiological activities such as immunity and metabolism. Through genomic analysis, it was identified that gut microbiota may reshape the tumor microenvironment by affecting miRNAs, thereby affecting the metastasis and prognosis of CRC (75,76).…”
Section: Regulatory Mechanism Metabolitesmentioning
confidence: 99%